An antithrombin replacement strategy during asparaginase therapy for acute lymphoblastic leukemia is associated with a reduction in thrombotic events. Issue 11 (1st November 2016) - Farrell, Katrina; Fyfe, Andrew; Allan, Jonathan; Tait, R. Campbell; Leach, Mike
Abstract: Thrombosis is a well-recognized complication of asparaginase therapy for acute lymphoblastic leukemia (ALL), associated with the depletion of antithrombin (AT). Following a high incidence of thrombotic episodes during induction therapy for ALL in our tertiary referral center, we prospectively instituted a protocol of AT replacement. Forty-five consecutive adolescents and adults with ALL treated with asparaginase-containing phase I induction protocols were included in this observational study. Fifteen received standard therapy with no replacement; the subsequent 30 were managed with the protocol described. One or more low AT levels (<70 iu/dl) were recorded in 76% of patients in the cohort managed using the protocol, resulting them in receiving an AT replacement. There was a significant reduction in the incidence of thrombosis with this strategy (0/30 vs. 5/15, p  < 0.001). We suggest that such a strategy should be studied in a prospective randomized sub-study within the context of a national ALL trial.